ANALISIS KINERJA DINAS PENDAPATAN, PENGELOLAAN KEUANGAN, DAN ASET KOTA SURAKARTA DALAM PEMUNGUTAN PAJAK HOTEL, RESTORAN, DAN HIBURAN TAHUN 2009 – 2014 BERDASARKAN KONSEP VALUE FOR MONEY - Fadjar Harimurti, Diyah Astuti Permatasari, Suharno & (Universitas Slamet Riyadi, 2016)
The purpose of this study is to analyze the financial performance of the Department of Revenue, Finance and Asset Management Surakarta perspective in terms of economy, efficiency and effectiveness of tax revenue the hotel, restaurant and entertainment by using the concept of Value For Money. This study uses secondary data with quantitative data analysis techniques based on the ratio of economy, efficiency and effectiveness and qualitative data that is on the Department of Revenue, Finance and Asset Management Surakarta. The results of the analysis based on the assessment criteria which refers to the Decree of the Minister of Interior number 690900-327 on Financial Performance Assessment guidelines, showing the performance of the Department of Revenue, Finance and Asset Management Surakarta Value For Money Concepts based on tax receipts hotels, restaurants and entertainment year average 2009 –2014 can be categorized as very economical, very efficient, and very effective. Efforts - the efforts made by the Department of Finance and Asset Management Revenue Surakarta is intensifying outreach Increase taxation to the taxpayer in order to understand even aware of the importance of Taxes Hotel, Restaurant and Leisure as one component of the Local Taxes are used to finance regional development.Keywords: Revenue, PAD, value for money, economy, efficiency, effectiveness